Hydroconversion of methylcyclohexane on TEOS-modified H-ZSM-5 zeolite catalysts: Production of a high-quality synthetic steamcracker feedstock - Berger, Christine; Raichle, Andreas; Rakoczy, Rainer A; Traa, Yvonne; Weitkamp, Jens (Microporous and mesoporous materials, 2003)
With the advent of the European Auto Oil Programme and comparable legislation in other parts of the world, the aromatics content of gasoline has to be reduced considerably. Therefore, new outlets for surplus aromatics have to be found. Mixed n-alkanes with two and more carbon atoms (C 2+- n-alkanes) represent a high-quality synthetic feedstock for steamcrackers. Thus, the hydrogenation of aromatics to cycloalkanes followed by their hydroconversion into C 2+- n-alkanes (predominantly ethane, propane and n-butane) could become a useful process option for converting surplus aromatics into a synthetic steamcracker feed. During hydroconversion of methylcyclohexane to C 2+- n-alkanes, the catalytic properties of acidic zeolite H-ZSM-5 can be remarkably improved by chemical liquid deposition of tetraethoxysilane. Thereby, the yield of the desired C 2+- n-alkanes at, e.g., 400 °C can be enhanced from around 77% to nearly 82%. Simultaneously, a drastic diminution of the concentration of external Brønsted acid sites and a significant decrease of the total concentration of Brønsted acid sites were observed by adsorption of, respectively, collidine and pyridine monitored by FTIR spectroscopy. Nitrogen adsorption experiments revealed a slight decrease of the micropore volume. These data are consistent with an extensive deactivation of the active sites on the external surface and in close proximity to the pore openings, the latter leading to pore mouth narrowing or, more likely, to partial pore mouth plugging.